Some characterization of glauconite in Syrian coastal phosphate - إبراهيم أحلام (Latakia University Journal -Basic Sciences Series, 2024)
The aim of the present study is to characterize the glauconite grains associated with the coastal chain phosphate that distinguish them from Palmyra phosphate, and to compare them between the three sites where it is spread: Ain al-Tineh, Ain Lillon (south of the Haffa area), and Qalaat al-Muhalaba (north of Qardaha. To achieve the objective of the study, a group of samples were collected from the study sites and microscopic thin sections were prepared, that were studied with polarizing microscopy in the laboratories of the Department of Geology at the Faculty of Science, Tishreen University. The shape and color of the glauconite grains were compared at the three sites. The potassium ratios were compared between the studied sites, which was analyzed in the laboratories of the Atomic Energy Commission – Damascus. The sedimentary medium in the coastal phosphate environment was suitable for the living of microbes and bacteria, working to stabilize the trivalent iron, aluminum and magnesium forming the characteristic green slurry of these grains in the first stage, then the microbes work to introduce potassium into the crystalline structure of metals and organic matter.